Study of adverse effects of extrapyramidal syndrome use of combination of antipsychotics antidepressants in outpatient schizophrenia patients in RSUP Fatmawati for the period 2016-2020 - Ema Nillafita Putri Kusuma; Emy Oktaviani; Windi Astutie Harahap (Pharmaciana, 2023)
Schizophrenia disorder is a serious mental disorder and chronic symptoms that have mixed of schizophrenia and mood symptoms. Schizophrenia affects the individual concerned. Schizophrenia has several symptoms that can cause social and occupational dysfunction, such as disruption of work or activities, lack of interpersonal relationships, decreased self-care skills, and mortality. This study was an observational study with a cross-sectional study design using secondary data in the form of medical records. The population of this study is 449 patients, and 126 patients met the inclusion criteria. The number of patients with age 20-35 years is 47.6%, 54% male gender, 96.8% take the drug by oral. The most common diagnosis of the patient with schizophrenia was paranoid schizophrenia 100 (79.4%), and got the most common extrapyramidal adverse effect in acute dystonia is 32.5%. The type of drug that may cause extrapyramidal adverse effects are the Risperidone antipsychotic in 90 (17.9%).  The results of the study showed that there was no significant relationship between the type of drug combination use and the incidence of adverse effects from extrapyramidal syndrome with a sig. 0.966> 0.05. Meanwhile, the number of drugs consumed by the patients did not have a significant relationship with the sig value. 0.119> 0.05. The Gender, patient age, method of administration, and diagnosis of schizophrenia did not affect the adverse effects of extrapyramidal syndrome with sig values of each gender (p=0.881), patient age (p=0.665), method of administration (p=0.920), and diagnosis of schizophrenia (p=0.908).